2022
DOI: 10.15201/hungeobull.71.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of place, memory and identity through urban place names in Banská Bystrica, Slovakia

Abstract: The paper looks at the renaming of streets as a significant aspect of post-socialist change using an example of the city of Banská Bystrica, Slovakia. It discusses politics, processes and practices of (de-re)commemoration in street names, which reflect transformations of memory (remembering and forgetting), identity, heritage, power and resilience related to public space in a post-socialist city. Changing street names creates new connections between the past and the present and reflects political power struggl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Similarly, the decrease of political and military place names in favour of toponymy exhibiting local topographical features, as well as peculiarities of local industry and culture, can be interpreted as a desire among renaming commission members to lower the degree of ideologisation and avoid any future renaming situations (Kudriavtseva, N. 2020). However, it should be noted that restoration of pre-socialist commonly used names and introduction of non-commemorative neutral names as dominant renaming strategies sometimes occur in relatively small post-socialist cities that hardly can be defined as geopolitically divided, e.g., Banská Bystrica (Bitušíková, A. 2022).…”
Section: Memory Politics In Ukraine and Geopolitical Fault-line Citiesmentioning
confidence: 99%
“…Similarly, the decrease of political and military place names in favour of toponymy exhibiting local topographical features, as well as peculiarities of local industry and culture, can be interpreted as a desire among renaming commission members to lower the degree of ideologisation and avoid any future renaming situations (Kudriavtseva, N. 2020). However, it should be noted that restoration of pre-socialist commonly used names and introduction of non-commemorative neutral names as dominant renaming strategies sometimes occur in relatively small post-socialist cities that hardly can be defined as geopolitically divided, e.g., Banská Bystrica (Bitušíková, A. 2022).…”
Section: Memory Politics In Ukraine and Geopolitical Fault-line Citiesmentioning
confidence: 99%
“…The other main area of research is the study of the spatial distribution of religious institutions, with particular attention paid to the geographical features of the settlements and focusing on the most important buildings used for religious purposes (churches, mosques, synagogues). Studies on the spatial structure of medieval towns have shown that these buildings, and in larger towns the central units (Christian religion-cathedral, Islamic religion-central mosque), were predominantly located in the central parts of the settlements, in order to meet the need for easy accessibility (Atikah et al 2022;Bitušíková 2022;Hronček et al 2022;Neumannová 2022;Sági 2022;Sjoberg 1955); this was observed both in the case of Christian churches (e.g., Nicholas 2003;Ballard 2005) and Islamic mosques (Ehlers and Floor 1993;Kheirabadi 2000). Furthermore, however, it has also been highlighted that smaller sub-centres were established in larger cities, of which church complexes constituted a substantial part (Gutiérrez 2015;Burtenshaw et al 2021).…”
Section: Introductionmentioning
confidence: 99%